Lackadaisy. Volume 2 - Butler, Tracy J., 1980- (Iron Circus Comics, 2024)
It's 1927 and Prohibition is in full effect in St. Louis, Missouri. Organized crime has risen to meet the relentless demand for illicit alcohol. Bootleggers, gangsters, and might-makes-right dominate the city's underworld, fueled by the patrons of speakeasies like Lackadaisy, run by the unstoppable force of widowed Mitzi May. Or at least, she seemed unstoppable until now. After a violent raid from a rival operation left bullet holes all over Lackadaisy and inside Mitzi's trusted confidante Viktor; the situation is getting desperate in the glamorous pleasure palace hidden under the unassuming Little Daisy Cafe. As her charms fail to secure new business partners and the faith of her posse waivers, ambitious external forces press ever closer in. The gang struggles to secure booze, "suss" out new connections, and recover from recent traumas, all while the walls keep closing in.--